The Deconstruction of Milk al-yamīn Muhammad Shahrūr and Abdul Aziz's Interpretation: Analysis of Maqāṣid al-Sharīah from the Perspective of Maslahat and Mafsadat - Muhammad Miqdad Al Ghifari Syatta; Ahmad Baehaki; Ida Fitri Anggarini (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2025)
The interpretations of milk al-yamīn proposed by Muhammad Shaḥrūr and Abdul Aziz have been characterized as liberal by various Muslim scholarly communities. This characterization stems from their apparent neglect of established interpretative methodologies and the disregard for the prevailing moral frameworks that have historically governed such exegeses. Consequently, their readings are perceived to align with the objectives of secular feminist discourse. In response, Abdul Mustaqim offers a critical evaluation of their work, identifying several key deficiencies, including ontological, methodological, ideological, and epistemological shortcomings. In light of these critiques, a more rigorous reassessment of Shaḥrūr and Abdul Aziz’s interpretations is warranted, particularly through the lens of maqāṣid al-sharīʿah (the objectives of Islamic law). Such an analysis aims to delineate the theoretical boundaries that these scholars may have transgressed. Employing a qualitative research design, this study examines Shaḥrūr’s Al-Kitāb wa Al-Qur’an alongside Abdul Aziz’s dissertation, utilizing theoretical and critical analytical techniques. The qualitative critical analysis facilitates a comprehensive understanding of the appropriate interpretative framework for milk al-yamīn.